Semantic annotation: mapping text to ontologies. (25th January 2008) - Poibeau, Thierry
This position paper discusses various issues concerning the semantic web. We claim that reflection on formats has attracted the most important part of the research effort so far, whereas the web (including the future semantic web) is mainly made of texts. From our point of view, research should attach a major role to natural language properties and deal with complexity, ambiguity and polysemy. We show that the initial model from T. Berners-Lee must be refined and made more complex if these natural language technologies are to take language diversity into account.